Improved Anti-Treg Vaccination Targeting Foxp3 Efficiently Decreases Regulatory T Cells in Mice. Issue 7 (September 2016) - Mousavi Niri, Neda; Memarnejadian, Arash; Pilehvar-Soltanahmadi, Younes; Agha Sadeghi, Mohammadreza; Mahdavi, Mehdi; Kheshtchin, Nasim; Arab, Samaneh; Namdar, Afshin; Jadidi, Farhad; Zarghami, Nosratollah; Hajati, Jamshid
Abstract : Introduction: The critical role of regulatory T (Treg) cells in dampening immune responses against tumor cells is apparent. Therefore, several methods have been introduced for eliminating Treg. Among them, inducing immune responses against Treg cells expressing Foxp3 transcription factor is a hopeful approach to decrease the frequency of Tregs. In current study, we used the chimeric FoxP3-Fc(IgG) fusion construct/protein to effectively stimulate the immune responses against Treg cells. Materials and Methods: Previously constructed FoxP3-Fc(IgG) DNA vaccine and its protein counterpart were injected into C57BL/6 mice in a prime/boost regimen. After 2 weeks, the mice were killed to measure the frequency of Tregs in their spleens, as well as analyze their specific cytokine production, T-cell proliferation, and CD8 + T-cell cytotoxicity against FoxP3 protein. Results: FACS analysis of FoxP3 + CD4 + cells in splenocytes revealed the efficiency of FoxP3 DNA-prime protein-boost strategy to decrease the Treg cells and further showed considerable superiority of Fc(IgG) fusion strategy. This significant reduction in Treg frequency was also concomitant with higher FoxP3-specific CTL and Th1 responses in FoxP3-Fc vaccinated animals. Conclusions: Prime/boost vaccination against FoxP3 in addition to enhanced antigen presentation by means of Fc fusion strategy could be successfully considered for Treg depletion studies. Validity of this approach should be experimentally tested in preclinical tumor models.